Ultrasonic bonding of thermoplastic microfluidic devices - Ngooi, Yaohe. (2013)
Microfluidic devices see many advantages in using plastics that include low cost and easily available manufacturing methods, as compared to glass and silicon. Regardless of the bonding method, mass manufacturing development always imposes a unique set of challenge to overcome.